THE LEARNING MOTIVATION AND PREFERRED LEARNING ACTIVITIES OF SUCCESSFUL STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM AT UNIVERSITAS BENGKULU. THESIS, ENGLISH EDUCATION STUDY PROGRAM, EDUCATION AND TEACHERS TRAINING FACULTY, BENGKULU UNIVERSITY - Pertiwi, Fitri Dwi (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2018)
This research aimed to find out the dominant kind of motivation in learning English, the preferred learning activities and the difference between the successful students with integrative and instrumental motivation on their preferred learning activities. This study was designed as descriptive quantitative method. The population of this research was the fifth and the seventh semester students of English Education Study Program at Universitas Bengkulu. The sample of this research was 34 successful students at the fifth and seventh semester students. The instruments of this research were questionnaire and questions list. The formula as recommended by Sudijono (2000) was used in data analysis. The result of this research showed that the successful students with integrative motivation were more dominant in learning English. The preferred learning activities of successful students have characteristic such as fun, entertaining and some of them are compulsory. There was no significant difference on the choice of preferred learning activities between the successful students who instrumentally and integratively motivated in learning English.